2016
DOI: 10.3389/fpubh.2016.00062
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How Substance Use Impedes Engagement along the HIV Care Continuum: A Qualitative Study

Abstract: Drug use is associated with low uptake of HIV antiretroviral therapy (ART), an under-studied step in the HIV care continuum, and insufficient engagement in HIV primary care. However, the specific underlying mechanisms by which drug use impedes these HIV health outcomes are poorly understood. The present qualitative study addresses this gap in the literature, focusing on African-American/Black and Hispanic persons living with HIV (PLWH) who had delayed, declined, or discontinued ART and who also were generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 54 publications
(63 reference statements)
2
40
0
Order By: Relevance
“…These findings are not surprising, as drug us is commonly used as a copy strategy for dealing with an HIV diagnosis 44 and can impede engagement in HIV care. 45 In previous research with HIV-infected YBMSM, researchers demonstrated a relationship between anxiety and alcohol and marijuana use, which contributed to poor medication adherence. 46 Substance use is a barrier to ART initiation and engagement in care, can reduce confidence in one’s medication management skills, and contribute to depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are not surprising, as drug us is commonly used as a copy strategy for dealing with an HIV diagnosis 44 and can impede engagement in HIV care. 45 In previous research with HIV-infected YBMSM, researchers demonstrated a relationship between anxiety and alcohol and marijuana use, which contributed to poor medication adherence. 46 Substance use is a barrier to ART initiation and engagement in care, can reduce confidence in one’s medication management skills, and contribute to depression.…”
Section: Discussionmentioning
confidence: 99%
“…46 Substance use is a barrier to ART initiation and engagement in care, can reduce confidence in one’s medication management skills, and contribute to depression. 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we did not find an association between transactional sex and HIV stigma as a barrier to PrEP use, we did not assess stigma specific to transactional sex or substance use, which may be more relevant as a barrier to PrEP use and healthcare access for this population [23, 24]. In fact, Underhill et al found that stigma associated with substance use was prevalent among MSM who engage in transactional sex, and that it was more commonly cited as a barrier to healthcare access and PrEP initiation than sexual behavior and HIV risk-related stigma [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, substantial disparities remain (Hall et al, 2013) since African-Americans and Hispanics are at greater risk for HIV infection (Giordano et al, 2010; Harrison, Song, & Zhang, 2010; Siddiqi et al, 2015), and for failure to achieve viral suppression once infected (Castel et al, 2016; Xia, Sun, Wiewel, & Torian, 2017). HIV-infected individuals with alcohol and drug problems are also more likely than others to have poor health behaviors (Crane et al, 2017; Metrik, Caswell, Magill, Monti, & Kahler, 2016; Young, Wood, Dong, Kerr, & Hayashi, 2015), lower engagement in and utilization of HIV care, and lower ART adherence (Gwadz et al, 2016; Lake et al, 2017; Lucas, 2011). Further, the dual use of illicit drugs and alcohol, more than the use of either one alone, is associated with poor quality of HIV care (Dickson-Gomez, Bodnar, Petroll, Johnson, & Glasman, 2015; Korthuis et al, 2012), viral resistance to treatment, and HIV disease progression (Azar et al, 2015; Baum et al, 2009; Lima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%